The Effect of Wordwall-Based Interactive Media on the English Vocabulary Mastery of Fifth Grade Students at UPT SDN 1 Bangkala Kabupaten Jeneponto - S, Anita.; Amin, Muhammad; Ramli, Abdul Malik (Invention: Journal Research and Education Studies, 2025)
This research is based on the low vocabulary mastery of fifth grade students at UPT SDN 1 Bangkala Kabupaten Jeneponto. This study employed a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The objectives were to describe the use of Wordwall in grade V; to describe vocabulary mastery; and to analyze the effect of Wordwall on vocabulary mastery. Descriptive analysis showed excellent implementation of Wordwall. Inferential analysis revealed a sig. (2-tailed) value of 0.000 < 0.05 with t-count > t-table (7.946 > 2.042), hence Ha was accepted. The conclusion is that Wordwall has a significant effect on students’ English vocabulary mastery.